Increasing ZIS Receipts through Transparency and Characteristics of BAZNAS and LAZ in Indonesia - Sarifah Meilidya Trie Ayu; Tenripada Tenripada; Lucyani Meldawati; Andi Chairil Furqan (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the increase in the collection of Zakat, Infaq, and Sedekah (ZIS) through transparency and the characteristics of BAZNAS and Amil Zakat Institutions (LAZ) in Indonesia. This study uses data from BAZNAS and LAZ in Indonesia, with a final sample of 410 observations. The sample was selected using a purposive sampling technique. The results indicate that higher levels of transparency have a positive effect on increasing ZIS collection. In addition, institutional characteristics play an important role in increasing ZIS collection. Better institutional characteristics are associated with greater improvements in ZIS collection. The implications of this study are closely related to efforts to enhance ZIS collection through strengthening the characteristics of ZIS management institutions, such as institutional status, organizational type, and operational age, in order to build public trust. Furthermore, ZIS management institutions need to prioritize transparency, particularly through the presentation of annual reports, performance reports, and audited reports, to demonstrate a high level of accountability. The optimization of websites as a medium for transparency also needs to be enhanced to reach a wider range of donors, especially younger generations, in the digital era. However, these findings have several limitations, as the transparency measures used are limited to annual reports, performance reports, audited reports, and websites, and therefore do not cover other aspects of transparency.